The urgency of zakat and waqf management for improvement public welfare - Zulko Irfan Nuriyan; Pujiatun Najiah (NUsantara Islamic Economic Journal, 2023)
Religious concepts such as zakat and waqf include both divine and social aspects, allowing their use for the good of society. And to make this happen, Waqf and Zakat management must be competent and accountable. Zakat and waqf can be used for human resource purposes, such as providing scholarship status for students, teachers and lecturers in their respective fields, including in the mustahiq zakat category. In particular, zakat and waqf collectors must have clear priorities and a well-defined program. Likewise, reporting (income and expenditure) must be expressed clearly and firmly in order to increase understanding of muzakki and waqif.